Dynamics of 3D isolated thermal filaments. (3rd October 2016) - Walkden, N R; Easy, L; Militello, F; Omotani, J T
Abstract: Simulations have been carried out to establish how electron thermal physics, introduced in the form of a dynamic electron temperature, affects isolated filament motion and dynamics in 3D. It is found that thermal effects impact filament motion in two major ways when the pressure perturbation within the filament is supported primarily through a temperature increase as opposed to density: they lead to a strong increase in filament propagation in the bi-normal direction and a significant decrease in net radial propagation. Both effects arise from the temperature dependence of the sheath current which leads to a non-uniform floating potential, with the latter effect supplemented by faster pressure loss. The reduction in radial velocity can only occur when the filament cross-section loses angular symmetry. The behaviour is observed across different filament sizes and suggests that filaments with much larger temperature perturbations than density perturbations are more strongly confined to the near SOL region.